2022
DOI: 10.1088/2634-4386/ac830c
|View full text |Cite
|
Sign up to set email alerts
|

An organic synaptic circuit: toward flexible and biocompatible organic neuromorphic processing

Abstract: In the nervous system synapses play a critical role in computation. In neuromorphic systems, biologically inspired hardware implementations of spiking neural networks, electronic synaptic circuits pass signals between silicon neurons by integrating pre-synaptic voltage pulses and converting them into post-synaptic currents, which are scaled by the synaptic weight parameter. The overwhelming majority of neuromorphic systems are implemented using inorganic, mainly silicon, technology. As such, they are physicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Quite recently, Hosseini et al developed a biologically realistic spiking synaptic circuit, namely differential-pair integrator synapse, using mechanically flexible and biologically compatible complementary organic electronics. [210] By fabricating DNTT-based POFETs on flexible polyimide substrates, the authors used an organic synapse to successfully demon-strate the conversion of somatic voltage spikes (time constants reaching in excess of 2 s) into linearly proportional output current. By applying input spikes of different frequencies, the authors showed synaptic circuit response, and concluded that synaptic time constants similar to the time constants of the neuron's membrane potential are crucial in distinguishing different temporal input spike patterns.…”
Section: Application In Neuromorphic Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently, Hosseini et al developed a biologically realistic spiking synaptic circuit, namely differential-pair integrator synapse, using mechanically flexible and biologically compatible complementary organic electronics. [210] By fabricating DNTT-based POFETs on flexible polyimide substrates, the authors used an organic synapse to successfully demon-strate the conversion of somatic voltage spikes (time constants reaching in excess of 2 s) into linearly proportional output current. By applying input spikes of different frequencies, the authors showed synaptic circuit response, and concluded that synaptic time constants similar to the time constants of the neuron's membrane potential are crucial in distinguishing different temporal input spike patterns.…”
Section: Application In Neuromorphic Systemsmentioning
confidence: 99%
“…The performance of a ring oscillator is characterized by its high oscillation frequency and low stage delay (where circuit speed = 1/stage delay) to ensure implementation in next-generation sensing, clocking, or communication applications. [220] An example of a flexible Inverter VOFET [152] POFET [93,193] Oscillator POFET [90,93,193] Amplifier POFET [194,195] 4.2 Light-emitting devices OLED/AMOLED POFET [58,196] VOFET [144,197] Rollable displays POFET [58] Quantum-dot systems VOFET [144] Multiphoton emission OLEDs POFET [48] 4.3 Memory devices Floating gate POFET [87,198] Flash POFET [87] Ferroelectric VOFET [199,200] POFET [201] Optical VOFET [202] 4.4 Sensors Photo-/image sensors VOFET [88,[203][204][205] POFET [206,207] Biological sensors POFET [50,208] Neuromorphic systems POFET [209,210] VOFET [211] Gas sensors POFET [212] five-stage ring oscillator prepared on a flexible PEN substrate is shown in Figure 7f. [221] In a recent report that developed a bioinspired flexible artificial afferent nerve, organic ring oscillators were used to convert pressure stimuli into voltage pulses that oscillated at frequencies corresponding to the other circuit components.…”
Section: Background and Fundamental Organic Circuitsmentioning
confidence: 99%
“…Organic memristive devices and neuromorphic transistors are of special interest due to their unique set of characteristics, including relatively low operational voltage, mechanical flexibility, softness of devices, biocompatibility of materials, and ability to form three-dimensional structures [14][15][16][17]. In addition, they enable a variety of fabrication and processing techniques, ranging from spray-coating to inkjet and 3D printing, allowing fast and cost-effective production of devices [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Mimicking spiking behavior is an important step towards artificial systems operating at the interface with biology. In Hosseine et al [3] the authors show a biologically realistic spiking synaptic circuit on a biocompatible flexible substrate.…”
mentioning
confidence: 99%